The Chemmotology of New Generation Synthetic Liquid Fuels; Chemistry and Technology of Fuels and Oils; Vol. 60, iss. 6 - Strizhak P. A. Pavel Alexandrovich; Antonov D. V. Dmitry Vladimirovich; Aldoshin S. M. Sergey Mikhailovich; Yanovskii L. S. Leonid Samoylovich (2025, 2025)
Recent Russian advances in the development of synthetic liquid fuels are analyzed. This work is compared with research in other countries. Promising raw materials and technologies for synthetic liquid fuels are presented. The major requirements for suitable fuels are formulated. The controlled properties and characteristics of the full life cycles are listed: preparation, storage, transport, spraying, combustion, and minimization of harmful emissions. Optimized methods and steps for testing new generation fuels are formulated taking account of limited production volumes. Recommendations are offered for furthering the development of synthetic liquid fuels